Enhancing the thermoelectric properties of Sr1−xPr2x/3□x/3TiO3±δ through control of crystal structure and microstructure. (26th August 2019) - Ekren, Dursun; Azough, Feridoon; Freer, Robert
Abstract : A-site deficient perovskites are among the most important n -type thermoelectric oxides. Ceramics of Sr1− x Pr2 x /3 □ x /3 TiO3 ( x  = 0.1–1.0) were prepared by solid-state reaction at 1700–1723 K using highly reducing atmospheres. Samples with the highest Sr content had a cubic crystal structure ( P m 3 ¯ m ) ; incorporating Pr with A-site vacancies led to a reduction in symmetry to tetragonal ( I4/mcm ) and then orthorhombic ( Cmmm ) crystal structures. HRTEM showed Pr2/3 TiO3 had a layered structure with alternating fully and partially occupied A-sites and a short-range order along the (100) direction. Electrical conductivity was highest in samples of high symmetry ( x  ≤ 0.40), where the microstructures featured core-shell and domain structures. This enabled a very high power factor of approximately 1.75 × 10 −3  W m −1  K −2 at 425 K. By contrast, at high Pr content, structural distortion led to reduced electron transport; enhanced phonon scattering (from mass contrast, local strain and cation–vacancy ordering) led to reduced, glass-like, thermal conductivity. Carbon burial sintering increased the oxygen deficiency leading to increased carrier concentration, a maximum power factor of approximately 1.80 × 10 −3  W m −1  K −2 at 350 K and thermoelectric figure of merit of 0.26 at 865 K. The paper demonstrates the importance of controlling both crystal structure and microstructure to enhance thermoelectric performance. This article is part of a discussion meeting issue 'Energy materials for a low carbon future'.